2008
DOI: 10.1159/000170384
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Participate in 4-1BB-Mediated Suppression of Experimental Allergic Conjunctivitis

Abstract: Background: We showed previously that treatment with an agonistic anti-4-1BB Ab during the induction phase of murine experimental allergic conjunctivitis (EC) suppresses the development of this model disease. It was reported that 4-1BB promotes the expansion of regulatory T cells. Here we asked whether the suppression of EC by agonistic anti-4-1BB Ab treatment is mediated by regulatory T cells. Methods: Neonatal BALB/c mice were thymectomized and intraperitoneally injected with anti-CD25 Ab. At 6 weeks of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Stimulation of the 4-1BB pathway suppressed allergen-specific IgE production and AHR, through deletion of allergen-specific Th2 cells18). Therefore, it seems that 4-1BB could stimulate some regulatory signal to suppress the Th2 response as well21). In a different way, the present study also demonstrated the blockade of 4-1BB may attenuate an allergic inflammation.…”
Section: Discussionsupporting
confidence: 53%
“…Stimulation of the 4-1BB pathway suppressed allergen-specific IgE production and AHR, through deletion of allergen-specific Th2 cells18). Therefore, it seems that 4-1BB could stimulate some regulatory signal to suppress the Th2 response as well21). In a different way, the present study also demonstrated the blockade of 4-1BB may attenuate an allergic inflammation.…”
Section: Discussionsupporting
confidence: 53%
“…If agonistic Abs to 4-1BB are given after Ag priming, this results in augmentation of T cell responses (21, 39). Conversely, administration of Abs agonistic for 4-1BB before or during priming results in suppression of Ag-specific responses (21, 40, 41). This blunting of pathogen-specific responses has been reported to be TNF-α dependent (21).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, an unexpected finding that has been revealed in the field of 4-1BB agonism is the ability to shut off or limit autoimmune and other inflammatory reactions. This has been seen with agonist antibodies injected into murine models of SLE ( 7 , 8 , 136 ), MS ( 31 , 137 ), RA ( 16 , 138 ), conjunctivitis ( 139 , 140 ), IBD ( 141 ), uveitis ( 142 , 143 ), asthma ( 31 , 144 , 145 ), type I diabetes ( 146 ), chronic GVHD ( 147 ), diet-induced obesity ( 148 ), psoriasis ( 149 ), and Sjogren’s syndrome ( 150 ). In general, suppression driven by anti-4-1BB has been seen during the initiation phases of the disease rather than with therapeutic intervention during active disease, although in some models, therapeutic activity has been noted ( 8 , 138 ).…”
Section: Agonizing 4-1bb In Autoimmunitymentioning
confidence: 83%
“…Two primary mechanisms of 4-1BB-driven suppression have been suggested, either promoting the accumulation and activity of conventional CD4 + Foxp3 + Treg that can express 4-1BB, or more in-line with the tumor and virus literature on 4-1BB, inducing the differentiation or reactivation of CD8 T cells, either into CTL or a type of CD8 + Treg that makes IFN-g and can suppress the normal inflammatory response of CD4 T cells or B cells (16,22,140,141,143,144,(151)(152)(153)(154). Other suppressive activities such as directly driving death of pathogenic effector T cells, expanding MDSC, or promoting regulatory activities in dendritic cells, have also been suggested (19,20,142,147,155).…”
Section: Agonizing 4-1bb In Autoimmunitymentioning
confidence: 99%